2021
DOI: 10.3390/ma14113001
|View full text |Cite
|
Sign up to set email alerts
|

A Method for the Evaluation of Early Osseointegration of Implant Materials Ex Vivo: Human Bone Organ Model

Abstract: In the present work, an ex vivo organ model using human bone (explant) was developed for the evaluation of the initial osseointegration behavior of implant materials. The model was tested with additive manufactured Ti6Al4V test substrates with different 3D geometries. Explants were obtained from patients who underwent total knee replacement surgery. The tibial plateaus were used within 24 h after surgery to harvest bone cylinders (BC) from the anterior side using hollow burrs. The BCs were brought into contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
1
3
0
1
Order By: Relevance
“…These osteocytes appeared morphologically comparable to uncultured samples, therefore assuming viable osteocytes. This is in line with Zankovic et al who found viable osteocytes after 28 days of bone explant culture [77]. It would be of interest to study interactions between the bone cell types remaining within the explants as for example, previous research suggested that living osteocytes inhibit bone resorption ex vivo [78].…”
Section: Discussionsupporting
confidence: 78%
“…These osteocytes appeared morphologically comparable to uncultured samples, therefore assuming viable osteocytes. This is in line with Zankovic et al who found viable osteocytes after 28 days of bone explant culture [77]. It would be of interest to study interactions between the bone cell types remaining within the explants as for example, previous research suggested that living osteocytes inhibit bone resorption ex vivo [78].…”
Section: Discussionsupporting
confidence: 78%
“…To the best of the authors' knowledge, most of the in vitro studies related to osteointegration properties of a biomaterial are still focused on the use of cell cultures in monolayer or direct and indirect co-cultures seeded onto biomaterials [24,26,[31][32][33] to evaluate the effects of tested materials or part of them on viability, morphology, gene/protein expression, and commitment; the set-up of complex tissue cultures mimicking implant osteointegration is still limited. Recently, Zankovic et al and Przekora et al performed human bone organ cultures with implanted biomaterials made of 3D-printed Ti6Al4V disks and chitosan/curdlan/hydroxyapatite for 28 and 46 days, respectively, in static conditions [34,35]. In the study by Zankovic et al, although the tested material (TiAlV) is similar to the negative control used in the present study, the in vitro construct utilized an agarose mould, and the bone tissue originated from the tibial plateau.…”
Section: Discussionmentioning
confidence: 86%
“…This could aid in gaining increased knowledge of potential treatment effects. To enhance clinical relevance, it would be valuable to include human explant samples, which could be obtained from left-over bone tissue from surgeries, such as femoral heads or tibia plateaus (Swarup et al, 2018; Zankovic et al, 2021). Overall, the platform has the potential to be implemented in the preclinical testing phase of novel therapies preceding in vivo experimentation, thereby reducing and refining the number of animal studies needed.…”
Section: Discussionmentioning
confidence: 99%